Strategies to Boost Agricultural Entrepreneurship Productivity Through Mapping Priority Entrepreneurship Ecosystem Elements - tapsi, syhabuddin al; Baga, Lukman Mohammad; Feryanto (AFEBI Management and Business Review, 2024)
The agricultural sector, although a key pillar of Bogor Regency's economy, contributes relatively less compared to other industries, largely due to limited entrepreneurial capabilities and an underdeveloped entrepreneurship ecosystem. This study aims to identify strategic priorities for enhancing agricultural entrepreneurship productivity through ecosystem strengthening. Using Importance-Performance Map Analysis (IPMA) on data collected from 110 agricultural entrepreneurs, the results indicate that while networking elements exhibit strong performance, several critical areas require strategic intervention. Specifically, promoting a research-driven entrepreneurial culture, expanding market access, empowering intermediary institutions, and reinforcing ecosystem leadership are essential. Strengthening these elements is expected to foster a more dynamic and sustainable entrepreneurial environment, ultimately accelerating the agricultural sector's transformation within the service-based economy. Keywords: Demand, Entrepreneurial Culture, Intermediaries, Leadership, Networks.